The Values of Islamic Education and Science Learning in the Tradition of Jeleng Minyak 1000 Hajat - S. Ali Jadid Al Idrus; Lenny Herlina; Mohan Taufiq Mashuri (Postgraduate, University of Mataram, 2023)
The purpose of this research is to find outthe values ​​of Islamic education and science learning are integrated in the 1000 Hajat oil jeleng tradition at the Thohir Yasin Islamic Boarding School Lendang Nangka, East Lombok, West Nusa Tenggara. This research is a qualitative research. The selected informants are the chairman of the foundation and the perpetrators of making oil jars and have directly experienced the effects of complementary medicine using oil jars. Data collection techniques are observation, in-depth interviews and documentary studies.Observations were made on the activity of making jeleng oil among Thohir Yasin Islamic boarding schools. The results of the research show that during the manufacture of jeleng oil accompanied by readings that are adjusted according to the stages, then continue reading the prayers. At the start of the warm-up until it finishes reading the letters are Yasin, Assajadah, Addukhan, Almulk which are read continuously. Science lessons that can be obtained from the process of making Jeleng Oil are from the materials used contain various chemical substances and there are physical changes in its manufacture. Jeng oil has also been shown to be able to treat various diseases based on the effectiveness of chemical compounds from various ingredients, namely coconut, senna leaves and saffron